Digital transformation as a catalyst for enhancing business agility in the service sector: The mediating roles of business performance and competitive advantage - Bhattarai , Ujjwal; Sthapit, Arhan; Timsina, Baburam; Gurung, Oshin (American Journal of STEM Education, 2026)
Grounded in Dynamic Capabilities and Resource-Based View (RBV) theory, this study explores how digital transformation influences business agility in the service sector through the mediating effects of business performance and competitive advantage. To test the hypothesized model, cross-sectional data were purposively collected from 394 respondents across five diverse service sectors (i.e., education, Healthcare, Bank and Financial Institutions, Hospitality, and IT) operating in the Kathmandu Valley. The data were analyzed using SmartPLS 4.0. The findings indicate that digital transformation, business performance, and competitive advantage are significant predictors of business agility. Further, business performance and competitive advantage mediated the interplay between digital transformation and business agility. This study advances the digital transformation study by integrating strategic management principles to explain business agility drivers, emphasizing technology, talent, customer focus, and policy support to strengthen competitiveness in the service sector.